Breaking the diagnosis of cystic fibrosis to parents: A process not a one-off event. (September 2020) - Bryon, Mandy
Abstract: Breaking the news to parents that their child has cystic fibrosis [CF] is most frequently given in the first few weeks of the baby's life as a result of newborn screening. This is optimal to reduce morbidity but can have a significant impact on the parents' mental wellbeing and the parent–child relationship. Parent feedback indicates that assimilating the diagnosis is not a one-off event but a process that takes time. CF professionals therefore need to be aware not only of how they communicate the diagnosis initially but also the ways in which families make sense of this throughout at least the following year. The parent–patient–team relationship is essential to good health outcomes. Key objectives of this paper are to enable: (1) understanding parental responses to the diagnosis which can indicate how well they are managing CF for their child, (2) improving the way in which the diagnosis is communicated and, (3) changing team management of CF in the early years to include parental collaboration to support better mental and physical outcomes.